Gambaran Karakteristik Penderita Covid-19 di Kabupaten Pangandaran - Dinda Anindita Salsabilla; Feri Yuda Anggara (UPT Publikasi Ilmiah Unisba, 2023)
The World Health Organization (WHO) has declare COVID-19 as a Public Health Emergency International Concern. Data on Covid-19 cases (New All Record) at the Pangandaran District Health Office as of August 31 2022, which were confirmed positive, totaled 6,051 cases with 156 deaths. This study aims to describe the characteristics of COVID-19 sufferers in Pangandaran Regency. This study uses a cross sectional research design. The data used is secondary data recorded in the New All Record (NAR) Application. Characteristics of COVID-19 sufferers include 57.6% female and 42.4% male, the majority are aged 26-35 years, namely 1,259 people (20.9%), while the least are in the age range 0-5 years as many as 155 people (2.6%). Characteristics of COVID-19 sufferers in Pangandaran Regency based on their final death status were 156 people (2.6%) with the majority being female (54.5%) and aged 56-65 years (28.8%). The conclusion in this study is that the majority of COVID-19 case sufferers who died in Pangandaran district were female and aged > 50 years.